Problems of Directing Students to Professions in The Public Education System and Their Solutions - Iroda Mukhiddinovna Ashirmatova (Academia One Publishing, 2023)
The article provides information on the problems of vocational orientation of students in the public education system and their solutions.
Keywords: occupation; craft; experience; learning